Electrochemical degradation of DCF by boron-doped diamond anode degradation mechanism, pathways and influencing factors - Qiu, Huimin (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
Nonsteroidal anti-inflammatory drugs (NSAIDs) have been widely detected in wastewater and surface water, indicating that the removal of NSAIDs by wastewater treatment plants was not efficient. Electrochemical advanced oxidation technology is considered to be an effective process. This study presents an investigation of the kinetics, mechanism, and influencing factors of diclofenac (DCF) degradation by an electrochemical process with boron-doped diamond anodes. Relative operating parameters and water quality parameters are examined. It appears that the degradation follows the pseudo-first-order degradation kinetics. DCF degradation was accelerated with the increase of pH from 6 to 10. The degradation was promoted by the addition of electrolyte concentrations and current density. Humic acid and bicarbonate significantly inhibited the degradation, whereas chloride accelerated it. According to the quenching tests, hydroxyl radicals (•OH) and sulfate radicals contributed 76.5% and 6.5%, respectively, to the degradation. Sodium sulfate remains a more effective electrolyte, compared to sodium nitrate and sodium phosphate, suggesting the quenching effect of nitrate and phosphate on •OH. Major DCF transformation products were identified. According to the degradation products detected by liquid chromatography-mass spectrometry, hydroxylation and decarboxylation are the main pathways of DCF degradation; while dechlorination, chlorination, and nitro substitution are also included in this electrochemical degradation process